Analisis Strategi Pengolahan Limbah Medis saat Pandemi COVID-19 di Indonesia - Gitri Syiamil Awali; Sinta Ainun Rahma (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Indonesia reports an increase in the number of COVID-19 cases every day. As of December 20, 2020, confirmed cases reached 664,930 with 19,880 total cases of death. As the number of confirmed cases increases, it will result in an increase in medical waste such as medical masks, hazmat suits, gloves, and other infectious waste. The resulting infectious medical waste will have a negative impact, it can pollute the environment and expand the transmission of COVID-19. Therefore, a proper medical waste treatment strategy is needed so as not to expand the transmission of COVID-19, especially in Indonesia. This literature review was conducted to determine the medical waste treatment process carried out during the COVID-19 pandemic in Indonesia and to find out the standards for medical waste treatment, both nationally and internationally. The medical waste treatment strategy during the COVID-19 pandemic in Indonesia has not fully met the standards due to limited medical waste treatment facilities. Keywords : COVID-19, waste management, regulations, medical waste.